Chronic orofacial pain (COFP) disease or symptom? 2 - Gonzales, Theresa (Henry Stewart Talks, 2017)
Source of odontogenic and non–odontogenic pain, Neuropathic pain, Differential diagnoses of: trigeminal neuropathy, trigeminal neuralgia, trigeminal autonomic cephalalgias, Contemporary management strategies